1994
DOI: 10.1093/bja/72.1.17
|View full text |Cite
|
Sign up to set email alerts
|

Effects of 20% nitrous oxide on the ventilatory response to hypercapnia and sustained isocapnic hypoxia in man

Abstract: To examine the effects of a sub-anaesthetic concentration of nitrous oxide on ventilation, we have studied the ventilatory response to carbon dioxide and isocapnic hypoxia (FIN2O 0.2). In five subjects, we performed step decreases in PE'O2 to 6.7 kPa for 15 min and step increases in PE'CO2 (delta PE'CO2 1.5 kPa). The carbon dioxide responses were partitioned into a fast peripheral and slow central component. All control oxygen responses were biphasic: the acute hypoxic response was 7.2 (4.6) litre min-1 and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

1996
1996
2005
2005

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 17 publications
1
9
0
Order By: Relevance
“…This supports the findings of other investigators (39,42) who have found that the load-compensating respiratory reflexes important in maintaining ventilation during inspiratory resistive loading are not impaired by breathing mixtures containing up to 50% N 2 O. Moreover, in a recent study (13) in which the effects of 20% N 2 O on the ventilatory responses to hypercapnia were studied in five subjects, it was concluded that this subanesthetic concentration of N 2 O did not affect the peripheral chemoreflex loop.…”
Section: Influence Of Inert Gas Narcosis On Ventilationsupporting
confidence: 89%
“…This supports the findings of other investigators (39,42) who have found that the load-compensating respiratory reflexes important in maintaining ventilation during inspiratory resistive loading are not impaired by breathing mixtures containing up to 50% N 2 O. Moreover, in a recent study (13) in which the effects of 20% N 2 O on the ventilatory responses to hypercapnia were studied in five subjects, it was concluded that this subanesthetic concentration of N 2 O did not affect the peripheral chemoreflex loop.…”
Section: Influence Of Inert Gas Narcosis On Ventilationsupporting
confidence: 89%
“…In one article, the anaesthetic dose was uncontrolled [28], whereas in another, the anaesthetic (nitrous oxide) dose was 0.4 MAC [29]. The single articles referring to methoxyflurane [30], ether [30], desflurane [31] and nitrous oxide [32] were not included in the analysis. Finally, one article was excluded as it provided no data for a control group (i.e.…”
Section: Resultsmentioning
confidence: 99%
“…3). This analysis could be criticised for including the results of methoxyflurane and ether studies (neither of which are now in use) [10], and also for including two studies using N 2 O (which some might argue is not a true 'anaesthetic') [10,11]. However, excluding this data does not change the conclusions of the analysis.…”
Section: Critique Of the Quantitative Reviewmentioning
confidence: 99%
“…One of the suggested reasons for the difference in results was that Knill et al [1,2] had used Read's rebreathing method to induce hypercapnia (the end-tidal PCO 2 rises progressively over several minutes as air, or oxygenenriched air, is rebreathed from a large bag), whereas Dahan et al [3] used step hypercapnia (end-tidal PCO 2 rises rapidly to the desired level within seconds). Subsequent studies have explored these observations [4][5][6][7][8][9][10][11][12][13][14]. The original studies of Knill et al [1,2,5,10] found that some agents (N 2 O, enflurane and isoflurane) did indeed depress the ventilation-CO 2 response, but other agents (ether and methoxyflurane), like halothane, had no effect.…”
mentioning
confidence: 99%